2010
DOI: 10.1097/yco.0b013e328338620a
|View full text |Cite
|
Sign up to set email alerts
|

Do euthymic bipolar patients have normal cognitive functioning?

Abstract: Cognitive deficits of clinical relevance are documented for a substantial proportion, but not the majority, of bipolar patients. Yet, available data are inconclusive with respect to the origin of these deficits. Future studies on cognitive deficits in bipolar patients need to deliver detailed descriptions of drug treatment and clinical features.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
1
1

Year Published

2012
2012
2017
2017

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 50 publications
0
12
1
1
Order By: Relevance
“…Severe impairment is evident in those who have an early onset of illness and particularly the onset during childhood or adolescence. 17 We also observed no significant correlation between numbers of depressive episode and neurocognitive decline. Concurrent to present findings, in the systematic treatment optimization programme for early mania (STOP-EM) study, depressive episodes did not impart any additional burden on cognitive function.…”
mentioning
confidence: 55%
“…Severe impairment is evident in those who have an early onset of illness and particularly the onset during childhood or adolescence. 17 We also observed no significant correlation between numbers of depressive episode and neurocognitive decline. Concurrent to present findings, in the systematic treatment optimization programme for early mania (STOP-EM) study, depressive episodes did not impart any additional burden on cognitive function.…”
mentioning
confidence: 55%
“…Based on these previous findings, it may be inferred that BMI contributes to decreased cognitive functioning in euthymic individuals with BD. It is well established that impairments in executive function are apparent in mixed populations of individuals with BD as well as obese individuals without psychiatric disorders [7,10,16,19,22,26,27,28,41,45]. It could be hypothesized that obesity and BD are associated with common central nervous system structural and/ or functional changes in brain regions that subserve cognitive functioning.…”
Section: Discussionmentioning
confidence: 99%
“…Fourthly, there was no attempt to ''enrich'' the sample for individuals who have cognitive deficits. As a result, considerable heterogeneity in cognitive profiles was observed, which may have also decreased the likelihood of detecting an association [22] Fifthly, we did not have detailed information regarding the duration of overweight/obesity. Studies in non-psychiatric populations indicate that the adverse effect of overweight/obesity may be duration-dependent [19].…”
Section: Discussionmentioning
confidence: 99%
“…A number of research studies and meta-analyses suggest that signifi cant neurocognitive impairment is present during remission in many domains Bora et al 2009aBora et al , 2010aArts et al 2008 ;Jamrozinski 2010 ), in spite of some reservations (Gruber et al 2007 ;Kerr et al 2003 ). A meta-analysis reported that the illness phase had no effect on the short-term memory impairment (Goodwin and Jamison 2007 ), but some authors suggest that the impairment observed during the euthymic phase might be a consequence of antipsychotic medication alone (Jamrozinski et al 2009 ).…”
Section: The Effect Of Mood Symptomsmentioning
confidence: 96%
“…Overall, the severity of the disease is strongly related to neurocognitive function (Yates et al 2011 ). Onset in childhood or adolescence is related to more severe impairment (Jamrozinski 2010 ). In paediatric BD patients, a neurocognitive impairment is observed which is similar to adult patients (Dickstein et al 2004 ).…”
Section: The Effect Of Age and Age At Onset And Personal Psychiatric mentioning
confidence: 96%